EFFECT OF ROCK PHOSPHATE WITHOUT AND WITH ALUMINIUM INSTEAD OF DICALCIUM PHOSPHATE ON PERFORMANCE OF GROWING PULLETS - NAYAK, SUNIL; BAGHEL, R.P.S.; NAYAK, ANJU (Indian Journal of Animal Production and Management, 2017)
ABSTRACTDicalcium phosphate (DCP) is used traditionally as phosphorus supplement in poultrydiets. However, due to high demand and scarce availability, its cost is steeply increasing.Therefore, to reduce the cost of mineral mixture, it has become imperative to use alternateand economical phosphorus supplement in poultry diet without lowering the productionperformance of birds and reducing the cost of their production. One of the alternates is rockphosphate (RP) which is available in plenty at much lower cost compared to DCP. Theperformance of birds on RP varies greatly probably because of large variations in thefluorine (F) content (205 to 5540 mg/kg) of the diets based on RP. Therefore, this study hasbeen planned to see the utilization of rock phosphate instead of dicalcium phosphate on thegrowth performance of egg type growing chicken. In the experiment, three hundred andtwenty four WLH growing pullets (08 weeks age) were randomly distributed to 27 replicatesof 12 pullets each and were allotted to 9 dietary treatments. Diet one (T1) was control. Diets2, 4, 6 and 8 (T 2, T4, T6 and T8) were same as T1 except that in these diets DCP wasreplaced @ 40%, 60%, 80% and 100% with rock phosphate. While, diets 3, 5, 7 and 9 (T 3,T5, and T7and T9) were same as T 2, T4, T6 and T8 accept the addition of aluminium at aratio of 0.8 Al: 1 F, in those diets. Experiment was conducted for 9-20 weeks (Growerphase). The overall performance of growers offered RP diets indicated that increase in thelevel of RP reduced their performance (weight gain, feed intake, FER and PI), significantly.However, it was significant when level of RP was increased above 40%. 60% replacement ofDCP with RP supplemented with aluminium sulphate did not influence the weight gain, feedintake FER and PI and led to better performance in growers. The cost per kg weight gainhas certainly increased due to use of higher levels of RP supplemented with aluminiumsulphate.Hence it was concluded that 40% RP and 60% RP along with aluminium sulphatewas beneficial to replace DCP in the mineral mixture of egg type growers. However,supplementation of aluminium sulphate to RP was not economical.Key wards : Alternate phosphorus sources, Aluminium sulphate, Dicalcium phosphate, Eggtype growers, Mineral mixture, Rock phosphate.